2012
DOI: 10.1177/1354856511419916
|View full text |Cite
|
Sign up to set email alerts
|

Ethical harm in virtual communities

Abstract: This article analyzes under which conditions ethical relevant avatar harm occurs in virtual worlds. The authors argue that this is most likely to occur when there are some norms of acceptable behavior in a virtual world and when players see avatars as constitutive to their identity. Other than online environments characterized by a ‘caveat emptor’ approach, Second Life is governed by certain norms of acceptable behavior. While Second Life inhabitants do not see a need for an additional code of ethics for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Virtual worlds provide an immersive experience and a compelling sense of presence (Loomis et al, 1999), inhabited by avatars controlled by their real-world users (Sadler, 2017). Engagement in virtual worlds is predicted to dramatically reshape our conception and experience of self (R. Gilbert & Forney, 2013), providing insights for social and cultural innovation (Vanacker & Heider, 2012). Psychological research in virtual worlds has already commenced, for example, suggesting that comorbidity between internet addiction and various forms of real-world addictions may apply to 3D virtual worlds (see R. L. .…”
Section: Virtual Worldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Virtual worlds provide an immersive experience and a compelling sense of presence (Loomis et al, 1999), inhabited by avatars controlled by their real-world users (Sadler, 2017). Engagement in virtual worlds is predicted to dramatically reshape our conception and experience of self (R. Gilbert & Forney, 2013), providing insights for social and cultural innovation (Vanacker & Heider, 2012). Psychological research in virtual worlds has already commenced, for example, suggesting that comorbidity between internet addiction and various forms of real-world addictions may apply to 3D virtual worlds (see R. L. .…”
Section: Virtual Worldsmentioning
confidence: 99%
“…Individuals may identify with their avatar (Vanacker & Heider, 2012) and have a moral attachment to the avatar (Wolfendale, 2007). The implication of human-avatar identity involvement and attachment represents a risk of psychological harm to the human behind the avatar (Vanacker & Heider, 2012).…”
Section: Virtual Worlds and Ethical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Virtual Reality frontiersin.org 2018) also discussed such criminal harassment to avatars targeted at female players, and reported that in Second Life, this kind of harassment has become so prevalent that developers need to publish a "primer" on how to avoid harm in such situations. Vanacker and Heider (2012) discussed the ethical issues raised from the harm done to avatars, including a case study of "The upskirt gallery," where a Second Life user took sneak peek photos and exhibited several "upskirt pictures" of other avatars he encountered in the virtual world.…”
Section: Violation Of Digital Bodiesmentioning
confidence: 99%
“…On the other hand, online environments are often regarded as a threat to children, because the opportunity to act anonymously causes misbehaviour (Livingstone et al, 2011;Vanacker and Heider, 2012). In public discourse, the worst scenarios are usually presented, such as violence, sexual abuse, dependence on the online environments and, thus, alienation from "the real life" (Herring, 2008).…”
Section: Introductionmentioning
confidence: 99%